2014
DOI: 10.1620/tjem.232.55
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Drainage with One Chest Tube Is Appropriate for Pulmonary Lobectomy: A Randomized Trial

Abstract: To expand postoperative residual lungs after pulmonary lobectomy, thoracic drainage with two chest tubes has been recommended. Several studies recently demonstrated that postoperative drainage with one chest tube (PD1) was as safe as that with two chest tubes (PD2). However, most of the patients in those studies underwent lobectomy by standard thoracotomy. Although the number of pulmonary lobectomies by video-assisted thoracic surgery (VATS) has been increasing in recent years, there have been no reports that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 10 publications
0
23
0
1
Order By: Relevance
“…Generally speaking, chest tube drainages were usually applied for patients suffering from pneumothorax who should be admitted to hospital following the failure of needle aspiration (3). And other indications for chest tube drainage included hemothorax (49,50), pleural effusion (51-53), pleural empyema (54,55), and major thoracic surgery (56)(57)(58). The approaches to insert chest tube drainage into body parts include axillary or anterior approach.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, chest tube drainages were usually applied for patients suffering from pneumothorax who should be admitted to hospital following the failure of needle aspiration (3). And other indications for chest tube drainage included hemothorax (49,50), pleural effusion (51-53), pleural empyema (54,55), and major thoracic surgery (56)(57)(58). The approaches to insert chest tube drainage into body parts include axillary or anterior approach.…”
Section: Discussionmentioning
confidence: 99%
“…According to the clinical evidences, the use of 2 chest tubes currently appears to be reasonable when a bilobectomy is performed, to allow a complete lung re-expansion, avoiding the risk of pleural spaces development, which is intrinsically present in this surgical procedure. A recent RCT, comparing patients with one or two chest tubes following lobectomy, demonstrated that there was no statistically significant difference in thoracentesis, the number of cases with pleurodesis, the amount and duration of drainage or the pain of the patients between one-tube and two-tube groups (19).…”
Section: Number Of Chest Tubesmentioning
confidence: 99%
“…The initial literature search yielded 738 citations, of which 5 studies were included (4 RCTs and 1 nRCTs) [ 3 7 ]. All eligible studies were published between 2003 and 2014.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically, single tube chest drainage is easier to insert and causes less pain and discomfort for the patient during both the insertion and while the tube is in the chest compared with double tube drainage, but single tube drainage has the possibility of inadequate chest drainage. Although some recent studies have compared the effectiveness of the two methods, there are no available data to support which of these treatments is more effective, and there are no evidence-based consensus recommendations for the optimal chest tube method to be used in pulmonary lobectomy [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%